(untitled) (Proceedings of International Conference on Special Education, 2015)
This study discusses teacher’s attitudes towards inclusive program in the mainstream setting. Service, confidence, challenges, and education policy were among the four factors measured in the overview of teachers who taught special education students in inclusive classes. This quantitative study involved 97 respondents. They answered randomly using an online application available in a few groups in Facebook. The results of the analysis found the tendency of mainstream teachers of giving good feedback with high percentages in service, confidence, challenges, and education policy. It is hoped that this study will benefit our education policy and also for the special education implementation, especially in inclusive settings. It will also benefit mainstream teachers by enhancing their teaching, as well as provide opportunities for special education students to receive better education